2020
DOI: 10.1002/da.23119
|View full text |Cite
|
Sign up to set email alerts
|

Elevated costly avoidance in anxiety disorders: Patients show little downregulation of acquired avoidance in face of competing rewards for approach

Abstract: Background Pathological avoidance is a transdiagnostic characteristic of anxiety disorders. Avoidance conditioning re‐emerged as a translational model to examine mechanisms and treatment of avoidance. However, its validity for anxiety disorders remains unclear. Methods This study tested for altered avoidance in patients with anxiety disorders compared to matched controls (n = 40/group) using instrumental conditioning assessing low‐cost avoidance (avoiding a single aversive outcome) and costly avoidance (avoida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 44 publications
(74 reference statements)
1
23
0
Order By: Relevance
“…However, it has been argued that their validity for costly avoidance in clinical settings is limited 6 , 9 . In support, we recently demonstrated that patients with anxiety disorders compared to matched healthy controls show similar levels of low-cost avoidance, but fail to reduce avoidance in presence of competing rewards for approach 10 . Thus, more and more studies apply approach-avoidance conflict tasks where approach is concurrently linked to varying aversive but also appetitive outcomes (e.g., monetary incentives).…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…However, it has been argued that their validity for costly avoidance in clinical settings is limited 6 , 9 . In support, we recently demonstrated that patients with anxiety disorders compared to matched healthy controls show similar levels of low-cost avoidance, but fail to reduce avoidance in presence of competing rewards for approach 10 . Thus, more and more studies apply approach-avoidance conflict tasks where approach is concurrently linked to varying aversive but also appetitive outcomes (e.g., monetary incentives).…”
Section: Introductionmentioning
confidence: 61%
“…However, little is known about the underlying decision process leading up to this behavior. In previous work, we found elevated avoidance in patients with anxiety disorders during approach-avoidance decision conflicts (i.e., when US-avoidance conflicted with gaining rewards) 10 . Interestingly, reward and threat contingencies were easily acquired and patients did not differ from matched controls during US-avoidance in absence of conflicting rewards.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Behavioural AAC studies that compare healthy and clinical populations are rare and results have been mixed, suggesting either greater avoidance in adults with anxiety disorders 29 or similar avoidance with greater response inconsistency in an adult transdiagnostic anxiety or depression sample. 30 Differences between AAC task paradigms might partially explain these mixed behavioural findings.…”
Section: E312mentioning
confidence: 99%
“…First, novel findings provide clinical utility as both strategies can be seen as proxies for therapeutic interventions. Instructions to “test whether a feared outcome does occur” can be seen as a laboratory proxy of the prediction-error based exposure rationale (Craske et al, 2022; Pittig et al, 2022; Pittig, Heinig, et al, 2021). Incentive-based extinction translates to therapeutic strategies emphasizing positive outcomes for approaching a feared situation.…”
Section: Introductionmentioning
confidence: 99%